2018
DOI: 10.1038/s41586-018-0686-x
|View full text |Cite|
|
Sign up to set email alerts
|

Predictable and precise template-free CRISPR editing of pathogenic variants

Abstract: Summary Following Cas9 cleavage, DNA repair without a donor template is generally considered stochastic, heterogeneous, and impractical beyond gene disruption. Here, we show that template-free Cas9 editing is predictable and capable of precise repair to a predicted genotype, enabling correction of human disease-associated mutations. We constructed a library of 2,000 Cas9 guide RNAs (gRNAs) paired with DNA target sites and trained inDelphi, a machine learning model that predicts genotypes and frequencies of 1- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

40
526
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 462 publications
(587 citation statements)
references
References 30 publications
40
526
1
1
Order By: Relevance
“…1E presents examples of the mutated alleles. This mutational landscape resembled profiles reported for chromosomal repair of CRISPR/Cas9 double stranded breaks by NHEJ in other mammalian cells (25). GenBank at NCBI assigned These sequence reads from amplicon-NGS libraries from the mutated PGRN locus of the DhuPGRN-H69 lines have been assigned the SRA accessions SRR9735031-34, BioProject ID PRJNA556235, and BioSample accession SAMN12344265.…”
Section: Progranulin Mutation In Cholangiocytes By Crispr Knockoutsupporting
confidence: 57%
“…1E presents examples of the mutated alleles. This mutational landscape resembled profiles reported for chromosomal repair of CRISPR/Cas9 double stranded breaks by NHEJ in other mammalian cells (25). GenBank at NCBI assigned These sequence reads from amplicon-NGS libraries from the mutated PGRN locus of the DhuPGRN-H69 lines have been assigned the SRA accessions SRR9735031-34, BioProject ID PRJNA556235, and BioSample accession SAMN12344265.…”
Section: Progranulin Mutation In Cholangiocytes By Crispr Knockoutsupporting
confidence: 57%
“…1a. Recently, several laboratories showed that CRISPR/Cas9 indel patterns and in-frame mutational probabilities are predictable from sgRNA-targeted DNA sequences 9,10 . Taking advantage of these findings, we first examined if the model is applicable to Munoz data.…”
Section: Essential Protein Domains Are Hyper-sensitive To Crispr/cas9mentioning
confidence: 99%
“…HPS pathogenesis and therapeutic options continue to be investigated, including through the use of organoids (Korogi et al, 2019; Strikoudis et al, 2019) and explorations of gene therapy (Ikawa et al, 2015; Iyer et al, 2019; Shen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%